2014
DOI: 10.1186/s13046-014-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib demonstrates broad anti-tumor activity in pre-clinical non-small cell and small cell lung cancer models

Abstract: BackgroundCarfilzomib (CFZ) is a proteasome inhibitor that selectively and irreversibly binds to its target and has been approved in the US for treatment of relapsed and refractory multiple myeloma. Phase 1B studies of CFZ reported signals of clinical activity in solid tumors, including small cell lung cancer (SCLC). The aim of this study was to investigate the activity of CFZ in lung cancer models.MethodsA diverse panel of human lung cancer cell lines and a SHP77 small cell lung cancer xenograft model were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…Carfilzomib (CFZ), a US FDA approved proteasome inhibitor, was used in this study as a model anticancer drug that is clinically relevant, nonfluorescent, practically insoluble (log p = 4.2) and unionizable in physiological conditions (pKa = 3.5). Traditionally, carfilzomib has been used to treat hematological malignancies such as multiple myeloma, but there is growing interest in the use of carfilzomib to treat solid tumors and tumor metastasis [30,31]. The NB-conjugated TNAs were designed to monitor the amount of drug remaining in the hydrophobic core of polymer nanoassemblies in solution in real time, and detect metastatic tumors in a tissue pH-dependent manner.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Carfilzomib (CFZ), a US FDA approved proteasome inhibitor, was used in this study as a model anticancer drug that is clinically relevant, nonfluorescent, practically insoluble (log p = 4.2) and unionizable in physiological conditions (pKa = 3.5). Traditionally, carfilzomib has been used to treat hematological malignancies such as multiple myeloma, but there is growing interest in the use of carfilzomib to treat solid tumors and tumor metastasis [30,31]. The NB-conjugated TNAs were designed to monitor the amount of drug remaining in the hydrophobic core of polymer nanoassemblies in solution in real time, and detect metastatic tumors in a tissue pH-dependent manner.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…To overcome these ill‐effects, efforts are being made to design selective inhibitors that specifically target immunoproteasome subunits 6 . From this perspective, the potential for the utilization of immunoproteasome inhibitors in the treatment of diseases is worth exploring 8 , 9 . Therefore, this review explores the relationship between the immunoproteasome profiles and various pathological conditions to guide future research.…”
Section: Introductionmentioning
confidence: 99%
“…Although the response to chemotherapy was poorer in C-SCLC compared to pure SCLC [4], the NCCN guidelines still recommend the etoposide and cisplatin as the first-line therapy of C-SCLC [5][6][7]. Interestingly, a recent study found that C-SCLC may have many of the features of NSCLC [8][9][10]. These results showed that the C-SCLC has its own clinicopathological characteristics.…”
Section: Introductionmentioning
confidence: 99%